Variação espacial e temporal do potamoplâncton ao longo do Rio Parnaíba (Piauí, Brasil): ferramentas ecológicas para o diagnóstico e monitoramento - Keppe, Isabela de Lima (Universidade Federal de São Carlos, 2022)
Here we test whether the Serial Discontinuity Concept actually predicts the damming effect as a gradient break in the Continuous River Concept. Microcrustaceans (Cladocera and Copepoda) were collected at six sampling points along 815 km of the main channel in a large tropical river (Rio Parnaíba, Northeast Brazil) for 2 years. The composition, diversity, abundance and dissimilarity were studied, as well as the effects of environmental variables. The hypotheses tested were: i) the presence of a single reservoir disrupts the structure of microcrustaceans, with greater richness at points downstream of the reservoir due to the mixture of lentic and lotic organisms, as well as at points in the downstream stretch of the river, as expected in the Serial Discontinuity Concept, increasing zooplankton diversity and abundance; ii) there is loss of species in areas close to the municipalities as a result of the impact of effluents (lower values of beta diversity and nesting effect). A total of 48 taxa (Cladocera = 37 species, Copepoda = 11 species) and 18 new records were found for the river, reflecting the positive effects on a wide spatial and temporal effort. Both hypotheses were accepted, with the effect of a reservoir causing a break in the continuous longitudinal gradient and the dissimilarity increasing at sampling points close to municipalities. The environmental variables showed low variation between the sampled points, with the temporal variation in the Parnaíba river being more evident. The presence of a single reservoir influences the increase in zooplankton diversity and abundance, as there is an increase in taxa in the downstream lotic environment, in addition to the influence on the flow.
Spatial and temporal variation of potamoplankton along the Rio Parnaíba (Piauí, Brazil): ecological tools for the diagnosis and monitoring
Keywords: Ecologia; Gradiente; Rio Parnaíba; Semiárido; Zooplâncton; Ecology; Gradient; Parnaíba River; Semi-arid; Zooplankton; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA